CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Yuan, Bo; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exons; Humans; INDEL Mutation; Retrospective Studies; Whole Exome Sequencing

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Sabo, Aniko; Murdock, David; Dugan, Shannon; Meng, Qingchang; Gingras, Marie-Claude; Hu, Jianhong; Muzny, Donna; Gibbs, Richard (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins; Whole Exome Sequencing

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Whole Exome Sequencing

Whole exome sequencing in a large pedigree with DCM identifies a novel mutation in . - Robyns, Tomas; Willems, Rik; Van Cleemput, Johan; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Breckpot, Jeroen; Devriendt, Koenraad; Corveleyn, Anniek (Acta Cardiol, 2020)
Familial dilated cardiomyopathy (DCM) is genetically heterogeneous and is associated with mutations in at least 40 different genes. Apart from encoding the giant protein Titin, none of these genes have an expected diagnostic yield of more than 5% complicating genetic diagnosis. Whole exome sequencing (WES) is a powerful alternative for the identification of the causal gene, however variant interpretation remains challenging. We report on WES in a large family with autosomal dominant DCM complicated by end stage heart failure and non-sustained ventricular arrhythmias in whom no causative mutation was identified using a targeted gene panel including 28 genes. WES was applied on 2 affected cousins. Stringent filtering of the identified genetic variants was performed including population variant frequencies, in silico analysis, orthologous and paralogous conservation. Subsequently Sanger sequencing was performed for 10 potential disease causing variants in order to confirm the presence of the variant and to evaluate co-segregation. Only one variant in exon 9 of the RBM20 gene (c.2714T > A, p.Met950Lys, NM_001334363) showed full co-segregation in the 7 affected family members resulting in a maximum 2-point LOD score of 2.1 and suggesting this as the pathogenic mutation responsible for the phenotype. Recently mutations in RBM20 have been linked to arrhythmogenic dilated cardiomyopathy caused by defective splicing of the giant sarcomere protein titin and abnormal calcium handling. We report the identification of a novel mutation in RBM20 by WES in a large pedigree with DCM.

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Yuan, Bo; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Yuan, Bo; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gözde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.

Prioritization of Candidate Genes for Congenital Diaphragmatic Hernia in a Critical Region on Chromosome 4p16 using a Machine-Learning Algorithm. - Callaway, Danielle A; Campbell, Ian M; Stover, Samantha R; Hernandez-Garcia, Andres; Jhangiani, Shalini N; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Muzny, Donna; Lally, Kevin P; Lupski, James R; Shaw, Chad A; et al. (J Pediatr Genet, 2018)
Wolf-Hirschhorn syndrome (WHS) is caused by partial deletion of the short arm of chromosome 4 and is characterized by dysmorphic facies, congenital heart defects, intellectual/developmental disability, and increased risk for congenital diaphragmatic hernia (CDH). In this report, we describe a stillborn girl with WHS and a large CDH. A literature review revealed 15 cases of WHS with CDH, which overlap a 2.3-Mb CDH critical region. We applied a machine-learning algorithm that integrates large-scale genomic knowledge to genes within the 4p16.3 CDH critical region and identified , , , , , , , and as genes whose haploinsufficiency may contribute to the development of CDH.

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Yuan, Bo; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Gibbs, Richard A; Muzny, Donna; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Muzny, Donna; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male; Whole Exome Sequencing

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gözde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, André; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Muzny, Donna; Uluc, Kayihan; Gibbs, Richard A; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gözde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Muzny, Donna; Yuan, Bo; Boerwinkle, Eric; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic Americans; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Muzny, Donna; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Launching genomics into the cloud: deployment of Mercury, a next generation sequence analysis pipeline. - Reid, Jeffrey G; Carroll, Andrew; Veeraraghavan, Narayanan; Dahdouli, Mahmoud; Sundquist, Andreas; English, Adam; Bainbridge, Matthew; White, Simon; Salerno, William; Buhay, Christian; Yu, Fuli; Muzny, Donna; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Massively parallel DNA sequencing generates staggering amounts of data. Decreasing cost, increasing throughput, and improved annotation have expanded the diversity of genomics applications in research and clinical practice. This expanding scale creates analytical challenges: accommodating peak compute demand, coordinating secure access for multiple analysts, and sharing validated tools and results. RESULTS: To address these challenges, we have developed the Mercury analysis pipeline and deployed it in local hardware and the Amazon Web Services cloud via the DNAnexus platform. Mercury is an automated, flexible, and extensible analysis workflow that provides accurate and reproducible genomic results at scales ranging from individuals to large cohorts. CONCLUSIONS: By taking advantage of cloud computing and with Mercury implemented on the DNAnexus platform, we have demonstrated a powerful combination of a robust and fully validated software pipeline and a scalable computational resource that, to date, we have applied to more than 10,000 whole genome and whole exome samples.
Keywords: Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Internet; Software

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Muzny, Donna; Boerwinkle, Eric; Gibbs, Richard; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface